Localisation of DNA sequences on plant chromosomes using PRINS and C-PRINS - Kubaláková, M; Vrána, J; Cíhalíková, J; Lysák, M A; Dolezel, J (Methods in cell science, 2001)
Localisation of DNA sequences to plant chromosomes in situ has traditionally been accomplished using fluorescence in situ hybridisation (FISH). Although the method is suitable for most applications it is time-consuming and requires labelled probes. Recently, primed in situ labelling (PRINS) has been developed as an alternative to FISH. PRINS is based on annealing of unlabelled oligonucleotide primer(s) to chromosome DNA and its elongation by DNA polymerase in the presence of labelled nucleotide(s). The method was found useful to detect high-copy tandem repeats on plant chromosomes. Low copy repeats were detected after a more sensitive variant of PRINS called cycling PRINS (C-PRINS), which involves a sequence of thermal cycles analogous to polymerase chain reaction. This paper describes protocols of PRINS and C-PRINS, which have been optimised for chromosome spreads and for chromosomes purified using gradient centrifugation and/or flow sorting. The methods result in clear signals with negligible non-specific labelling. Further work is needed to improve the sensitivity to allow for reliable detection of single- copy DNA sequences.
Keywords: DNA rostlinná; reprodukovatelnost výsledků; Microsatellite Repeats; mikrosatelitní repetice; Triticum; ječmen (rod); Sensitivity and Specificity; senzitivita a specificita; Telomere; DNA, Plant; pšenice; in situ značení DNA s primerem; Fabaceae; Reproducibility of Results; Hordeum; Primed In Situ Labeling; Magnoliopsida; telomery